Leadership and turnover intentions in a public hospital: The mediating effect of organisational commitment and moderating effect by activity department - Patrícia Martins; Generosa Nascimento; Ana Moreira (Administrative Sciences, 2023)
This research aimed to study the effect of leadership (transformational and transactional) on turnover intentions and whether this relationship is mediated by organisational commitment and moderated by the department of activity. To this end, it was hypothesized that: (1) leadership has a negative and significant association with turnover intentions; (2) leadership has a positive and significant association with affective organisational commitment; (3) organisational commitment has a negative and significant association with turnover intentions; (4) organisational commitment has a mediating effect on the relationship between leadership and turnover intentions; (5) the department to which the employee belongs has a moderating effect on the relationship between leadership and organisational turnover intentions. The sample consists of 477 participants working at the Hospital Professor Doutor Fernando Fonseca (HFF) in Portugal, performing their functions in several departments. This is a quantitative, correlational, and cross-sectional study. The results indicate that transformational leadership has a negative and significant effect on turnover intentions and a positive and significant effect on affective and normative commitment. Transactional leadership negatively and significantly affects all three components of organisational commitment. Affective and normative commitment has a negative and significant effect on turnover intentions. Calculative commitment has a positive and significant effect on turnover intentions. Affective commitment and calculative commitment have a partial mediating effect on the relationship between transformational leadership and organisational turnover intentions. The department to which the employee belongs does not have a moderating effect on the relationship between leadership and turnover intentions. It has been proven that leadership plays an extremely important role in the smooth running of this hospital unit.
Keywords: 350; department of activity; leadership; organisational commitment; turnover intentions